2021
DOI: 10.1097/md.0000000000026590
|View full text |Cite
|
Sign up to set email alerts
|

Personality as a predictor of HbA1c level in patients with type 2 diabetes mellitus

Abstract: Type 2 diabetes mellitus (T2DM) is the most common type of diabetes, accounting for around 90% of all cases worldwide. One means to strengthen the prevention and treatment of diabetes is via changes in self-management and lifestyle behaviors. However, lifestyle and personal health behaviors are strongly influenced by personality traits, and thus personality may play a significant role in such aspects as medication compliance, exercise habits, blood glucose monitoring, diet control, and maintenance of an ideal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…8,9 Related disease factors include duration of illness and hypoglycemia, while individual factors involve cognition, self-efficacy, and mood. [10][11][12][13][14] Relevant social factors include the availability of professional support and exercise environment. 15 Because elderly patients have spent a lifetime developing patterns and habits, it is important to determine how to move these individuals out of their comfort zone to participate in exercise regimens.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 Related disease factors include duration of illness and hypoglycemia, while individual factors involve cognition, self-efficacy, and mood. [10][11][12][13][14] Relevant social factors include the availability of professional support and exercise environment. 15 Because elderly patients have spent a lifetime developing patterns and habits, it is important to determine how to move these individuals out of their comfort zone to participate in exercise regimens.…”
Section: Introductionmentioning
confidence: 99%
“…. studies have found that TABP was associated with hypertension (34), hyperlipidemia (35), diabetes (36), alcohol consumption (37), and atherosclerosis (35), all of which may increase the risk of CSVD burden. We also found that TABP was positively correlated with WMH and EPVS but not LA and CMB, which may be due to the different pathogenesis of the four CSVD markers.…”
Section: Discussionmentioning
confidence: 99%
“… 32 This personality trait is also associated with a more significant initiative by the patient to use health applications, which helps them improve self-care in T2DM. 33 In addition, some studies report a lower percentage of body fat, lower total cholesterol level, 34 lower BMI, and higher glucose self-monitoring, 15 as well as a lower risk of mortality. 35 In this way, people with T2DM and greater openness might present more willing to give a change in routine that helps them control their disease.…”
Section: Discussionmentioning
confidence: 99%